Scaling and spatial complementarity of tectonic earthquake swarms - Passarelli, Luigi; Rivalta, Eleonora; Jonsson, Sigurjon; Hensch, Martin; Metzger, Sabrina; Jakobsdóttir, Steinunn S.; Maccaferri, Francesco; Corbi, Fabio; Dahm, Torsten (Earth and Planetary Science Letters, 2017)
Tectonic earthquake swarms (TES) often coincide with aseismic slip and sometimes precede damaging earthquakes. In spite of recent progress in understanding the significance and properties of TES at plate boundaries, their mechanics and scaling are still largely uncertain. Here we evaluate several TES that occurred during the past 20 years on a transform plate boundary in North Iceland. We show that the swarms complement each other spatially with later swarms discouraged from fault segments activated by earlier swarms, which suggests efficient strain release and aseismic slip. The fault area illuminated by earthquakes during swarms may be more representative of the total moment release than the cumulative moment of the swarm earthquakes. We use these findings and other published results from a variety of tectonic settings to discuss general scaling properties for TES. The results indicate that the importance of TES in releasing tectonic strain at plate boundaries may have been underestimated. This work received funding from the European Union through ERC Grant N. 240583. We thank Sigrún Hreinsdóttir (GNS Science) for providing the GPS time-series. The stimulating comments of two anonymous reviewers helped to improve the manuscript. Data from one seismometer was kindly provided by R.S. White from a project funded by the UK Natural Environment Research Council (NERC) SEIS-UK (loan 968). Data retrieved in this study are available in the supplementary information. The SIL earthquake catalog is available at www.vedur.is. All figures except for Fig. 7 are drawn using Generic Mapping Tools software (Wessel and Smith, 1998).